Towel for normal delivery operation kit and preparation method thereof
By using towels prepared with polyethylene, ABS resin and other materials, the problem of insufficient adsorption of non-woven towels is solved, efficient absorption and toughness are achieved, the number of replacements during surgery is reduced, and surgical efficiency and safety are improved.
Patent Information
- Application Number
- CN202411575280.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing non-woven towels do not adsorb the blood and amniotic fluid, which leads to frequent replacement during the operation, increasing the difficulty of surgical operation.
Towels are prepared using polyethylene, ABS resin, spherical microporous silica gel, glycerin monostearate, hydrogenated castor oil, compatibility agents, chitosan and activated carbon. The absorption of towels is improved by sharing and modifying activated carbon. Ability and toughness enhance antibacterial properties.
It significantly increases the amount of blood and amniotic fluid absorption by towels, reduces the number of replacements, improves surgical efficiency and safety, and has good toughness and comfort, reducing the risk of infection.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of towel processing for normal delivery surgical kits, and more specifically, to a towel for normal delivery surgical kits and a preparation method thereof. Background Art
[0002] A normal delivery surgical kit is a set of professional medical supplies prepared for normal delivery. It includes surgical gowns, gloves, sheets, towels, perineal pads, baby blankets, gauze, umbilical cord clamps, leg sleeves, and Meiya bags. The towels are used to absorb blood, amniotic fluid and other liquids during delivery to keep the surgical area clean and dry. Usually, towels are made of non-woven fabrics. The main reason is that due to their unique fiber structure and porosity, non-woven fabrics can quickly absorb and lock liquids, prevent the spread of blood, amniotic fluid and other liquids during surgery, and keep the surgical area clean and dry. At the same time, the production cost is low and suitable for large-scale use.
[0003] However, in actual use, it is found that the amount of blood and amniotic fluid adsorbed by non-woven fabrics is far less than the actual demand, resulting in the need to frequently change towels during surgery, which increases the difficulty of surgical operations. Summary of the invention
[0004] In order to solve the problem that existing non-woven towels absorb less blood and amniotic fluid during delivery, the present application provides a towel for a normal delivery surgical kit and a preparation method thereof.
[0005] In the first aspect, the present application provides a towel for a normal delivery surgical kit, which adopts the following technical solution: A towel for a normal delivery surgical kit is prepared from the following raw materials in percentage by weight: Polyethylene 30-40% ABS resin 10-15% Spherical microporous silica gel 10-20% Glyceryl monostearate 4-6% Pentaerythritol stearate 3-5% Hydrogenated castor oil 3-6% Compatibilizer 1-2% Chitosan 6-9% The remainder is activated carbon.
[0006] By adopting the above technical solution, the absorption capacity of the prepared towel for blood and amniotic fluid is greatly improved, and the number of towel changes during surgery is reduced. In the present application, polyethylene, ABS resin, spherical microporous silica gel, glycerol monostearate, hydrogenated castor oil, compatibilizer, chitosan and activated carbon are used together to form a towel, so that the absorption capacity of the towel is greatly improved. At the same time, the towel also has good toughness and softness, and is not easy to break after absorbing blood and amniotic fluid, ensuring the comfort of pregnant women during production.
[0007] Among them, polyethylene and ABS resin are used together, which makes the towel have good structural stability and toughness, preventing it from being damaged by pulling or squeezing during use. The unique microporous structure of spherical microporous silica gel is used to greatly improve the liquid absorption speed and capacity of the towel, ensuring that blood and amniotic fluid are quickly absorbed and locked. At the same time, the use of activated carbon enhances the towel's adsorption capacity for blood, amniotic fluid, and odor, keeping the surgical environment fresh. Glyceryl monostearate and pentaerythritol stearate work synergistically to promote the uniform mixing of polyethylene, ABS resin, spherical microporous silica gel, hydrogenated castor oil, compatibilizer, chitosan, and activated carbon, ensuring that the towel has a good effect of absorbing blood and amniotic fluid, and also has good structural stability. At the same time, the flexibility and hand comfort of the towel are improved, making the parturient feel more comfortable during the operation. Hydrogenated castor oil has good biocompatibility and antibacterial properties, can effectively inhibit bacterial growth, and protect parturients from infection. The addition of hydrogenated castor oil and chitosan gives the towel excellent antibacterial properties, effectively inhibiting bacterial growth and reducing the risk of infection. At the same time, chitosan itself also has certain adsorption properties. When used together with spherical microporous silica gel and activated carbon, it can further improve the adsorption capacity of towels. Hydrogenated castor oil is beneficial to increase the softness of towels.
[0008] Preferably, the activated carbon is modified activated carbon, which is prepared by the following method: 1) Soaking the activated carbon in hydrogen peroxide, filtering, and drying to obtain hydroxylated activated carbon; 2) mixing hydroxylated activated carbon, maleic anhydride, polyether polyol, initiator and solvent, stirring at 80-95° C. for 2-3 hours, filtering and drying to obtain grafted activated carbon; 3) Melting and kneading the grafted activated carbon and the first low-density polyethylene to obtain modified activated carbon.
[0009] By adopting the above technical solution, the compatibility of activated carbon with polyethylene and ABS is promoted, and the adsorption capacity of activated carbon is increased.
[0010] In step 1), the activated carbon is immersed in hydrogen peroxide to introduce hydroxyl groups on the surface of the activated carbon through an oxidation reaction. Hydroxylation not only increases the hydrophilicity of the activated carbon surface and improves the water absorption of the activated carbon, but also provides active sites for subsequent grafting reactions.
[0011] In step 2), hydroxylated activated carbon is mixed with maleic anhydride, polyether polyol, initiator and solvent, and stirred at high temperature. Maleic anhydride, as a polar monomer, can undergo grafting reaction with hydroxyl groups on the surface of activated carbon under the action of initiator to form grafted chains. At the same time, polyether polyol also participates in the reaction, further increasing the length and flexibility of the grafted chains. The surface of the grafted activated carbon is covered with a layer of organic polymer chains, and these chain segments have better compatibility with polyethylene and ABS molecular chains, thereby significantly improving the dispersion uniformity of activated carbon in polyethylene and ABS matrices.
[0012] In step 3), the grafted modified activated carbon is melt-mixed with the first low-density polyethylene, which not only further fuses the activated carbon and the polyethylene, but also makes the modified activated carbon more easily dispersed in the polyethylene and ABS blend system through the plasticizing effect of the low-density polyethylene, thereby improving the flexibility and adsorption of the towel.
[0013] Preferably, the weight ratio of the activated carbon, the maleic anhydride, the polyether polyol, the initiator, the solvent and the first low-density polyethylene is (7-15):(4-6):(2-5):(0.1-0.2):20:(2-3).
[0014] By adopting the above technical scheme, the amounts of activated carbon, maleic anhydride, polyether polyol, initiator, the solvent and the first low-density polyethylene are optimized, so that various raw materials can fully react, reduce raw material residues, promote the grafting of activated carbon, and improve the adsorption capacity and dispersibility of activated carbon.
[0015] Preferably, the average molecular weight of the polyether polyol is 2000-5000.
[0016] By adopting the above technical solution, the molecular weight of polyether polyol is optimized, which helps to better penetrate into the microporous structure of activated carbon during the grafting reaction, react with the hydroxyl groups on the surface of hydroxylated activated carbon, and further increase the length and flexibility of the grafted chain. If the molecular weight of polyether polyol is too large and the molecular chain is too long, it cannot penetrate into the interior of activated carbon and react with the hydroxyl groups on its surface; if the molecular chain of polyether polyol is too short, it will affect the length and flexibility of the grafted chain.
[0017] Preferably, the average particle size of the activated carbon is 200-800 nm.
[0018] By adopting the above technical solutions, the average particle size of activated carbon is optimized, the specific surface area of activated carbon is increased, the adsorption efficiency and capacity are improved, and thus the adsorption performance of activated carbon is increased. At the same time, the appropriate particle size range can improve its dispersibility, so that the activated carbon is more evenly distributed in the system, which helps its uniform distribution during mixing and processing, reduces agglomeration and agglomeration, and improves production efficiency and product quality.
[0019] Preferably, the particle size of the spherical microporous silica gel is 300-400 mesh, the internal structure pore volume is 0.8-1.3 ml / g, and the pore diameter is 80-120A.
[0020] By adopting the above technical scheme, the particle size, pore volume and pore size of spherical microporous silica gel are optimized, the adsorption performance, softness and comfort of the towel are improved, and its air permeability and moisture permeability are improved, which helps to keep the surgical area dry and comfortable. The 300-400 mesh spherical microporous silica gel particles are small, which helps to evenly distribute in the towel material, reduce the granularity, and thus improve the softness and comfort of the towel. This is especially important for surgical towels that need to come into direct contact with the patient's skin. The pore volume in the range of 0.8-1.3ml / g indicates that the spherical microporous silica gel has a high porosity, which is conducive to increasing its adsorption surface area and thus improving its adsorption capacity. In surgical towels, this helps to adsorb and remove possible odors, bacteria or other harmful substances, and keep the surgical environment clean and sterile. A pore size of 80-120A is very effective for adsorbing small molecules (such as bacteria, viruses, etc.). In the surgical environment, this helps to reduce the growth and spread of microorganisms.
[0021] Preferably, the polyethylene is obtained by mixing a second low-density polyethylene and a high-density polyethylene in a weight ratio of (4-6):9.
[0022] By adopting the above technical solution, the high-density polyethylene is known for its high strength and high toughness, while the second low-density polyethylene has good flexibility and impact resistance. The two are mixed in a ratio of (4-6):9, which can improve the flexibility and impact resistance of the towel while maintaining a certain strength, making it more durable. At the same time, the second low-density polyethylene has good melt fluidity, which helps to improve the fluidity of the material during processing, making the mixing more uniform and reducing the difficulty of processing, while the high-density polyethylene helps to maintain the shape stability of the material and prevent deformation during processing.
[0023] Preferably, the ASB resin contains 40-50% styrene, 10-30% acrylonitrile and 30-40% butadiene.
[0024] By adopting the above technical solution, the parameters of ABS resin are optimized, and the toughness and impact resistance are improved, making the towel more durable and less prone to damage during use; and the good thermal stability and chemical corrosion resistance ensure the stable performance of the towel during the disinfection and cleaning process.
[0025] Styrene gives ABS better melt fluidity, which is beneficial to the injection molding process of the towel, reducing processing difficulty and defects. Acrylonitrile improves the tensile strength and impact strength of ABS, improving the durability of the towel. At the same time, acrylonitrile improves the thermal stability of ABS, which helps the towel maintain stable performance at high temperature or during disinfection. Butadiene helps to increase the flexibility and impact resistance of the towel, improving the comfort of patients.
[0026] In a second aspect, the present application provides a method for preparing a surgical towel for normal delivery, using the following technical solution: A method for preparing a surgical towel for normal delivery, comprising the following preparation steps: S1, mixing polyethylene, ABS resin, spherical microporous silica gel, glycerol monostearate, pentaerythritol stearate, hydrogenated castor oil, a compatibilizer, chitosan and activated carbon to obtain a mixture; S2, feeding the mixed material into a twin-screw extruder to melt into a mixed melt; S3, feeding the mixed melt into a spinning machine, spraying it out from a spinneret to form filaments, and then cooling, stretching, and winding it through air blowing to obtain fibers; S4, combing the composite fibers into a web, and then subjecting the web to hydroentanglement and drying to obtain a towel for a normal delivery surgical kit.
[0027] By adopting the above technical scheme, polyethylene, ABS resin, spherical microporous silica gel, glycerol monostearate, pentaerythritol stearate, hydrogenated castor oil, compatibilizer, chitosan and activated carbon are fully mixed through step S1 to ensure the uniform distribution of the raw materials in the subsequent processing. Step S2 uses a twin-screw extruder for melting. The twin-screw extruder can effectively promote the melting and mixing of the raw materials with its high shear force, good dispersing and mixing ability and temperature control accuracy to form a uniform mixed melt. Step S3 uses a spinning machine to spin the mixed melt into fibers. Step S4 combs the composite fibers into a web, and uses hydroentanglement reinforcement technology to tightly combine the fiber web to form a solid towel substrate.
[0028] Preferably, in step S2, the temperatures of the heating zones of the twin-screw extruder are: 180-190°C in zones 1 to 3, 210-220°C in zones 4 to 6, 220-230°C in zones 7 to 8, and 210-220°C in zones 9 to 10.
[0029] By adopting the above technical solution, the temperature of the heating section of the twin-screw extruder is optimized so that the raw materials can be fully melted to form fibers with stable structure.
[0030] In summary, this application has the following beneficial effects: 1. High-efficiency absorption capacity: By combining the structural stability of polyethylene and ABS resin, the excellent liquid absorption performance of spherical microporous silica gel, and the strong adsorption capacity of activated carbon, the towel's absorption of blood and amniotic fluid is significantly improved, reducing the need for frequent towel changes during surgery and improving surgical efficiency and safety.
[0031] 2. Excellent toughness and durability: The combined use of polyethylene and ABS resin gives the towel excellent structural stability and toughness, which can withstand the pulling and squeezing during surgery and avoid damage.
[0032] 3. Excellent antibacterial properties: The combined effect of hydrogenated castor oil and chitosan enhances the antibacterial properties of the towel, effectively inhibits bacterial growth, and reduces the risk of postoperative infection in mothers.
[0033] 4. Good softness and comfort: Ingredients such as glyceryl monostearate, pentaerythritol stearate and hydrogenated castor oil improve the flexibility and feel of the towel, making the mother feel more comfortable during the operation and reducing the discomfort caused by the hardness of the material. DETAILED DESCRIPTION Example
[0034] Example 1 A towel for a normal delivery surgical kit is prepared by the following method: S1, 300 g of polyethylene, 150 g of ABS resin, 200 g of spherical microporous silica gel, 60 g of glycerol monostearate, 50 g of pentaerythritol stearate, 60 g of hydrogenated castor oil, 20 g of compatibilizer (maleic anhydride grafted ABS), 90 g of chitosan and 70 g of activated carbon (average particle size of 200 nm) were mixed to obtain a mixture; The molecular weight of polyethylene is 50,000; The ABS resin contains 40% styrene, 30% acrylonitrile, 40% butadiene, and has a molecular weight of 20,000. Maleic anhydride grafted ABS was purchased from Dongguan Shengli New Materials Co., Ltd. with model number XH6230JRJSAT.
[0035] The particle size of spherical microporous silica gel is 300-400 mesh, the internal structure pore volume is 0.8-1.3ml / g, and the pore diameter is 80-120A.
[0036] Hydrogenated castor oil was purchased from Wuhan Lingben Technology Co., Ltd. with a CAS number of 61788-85-0.
[0037] S2, feeding the mixed material into a twin-screw extruder to melt into a mixed melt; S3, feeding the mixed melt into a spinning machine, spraying it out from a spinneret to form filaments, and then cooling, stretching, and winding it through air blowing to obtain fibers; S4, combing the composite fibers into a web, and then subjecting the web to hydroentanglement and drying to obtain a towel for a normal delivery surgical kit.
[0038] In step S2, the temperatures of the heating zones of the twin-screw extruder are: 180°C for zones 1 to 3, 210°C for zones 4 to 6, 220°C for zones 7 to 8, and 210°C for zones 9 to 10.
[0039] The difference between Example 2-3 and Example 1 is that the types, amounts and parameters of some raw materials used to prepare the towels for normal delivery surgical kits are different. The specific differences are shown in Table 1: Table 1 Types, amounts and parameters of raw materials used in preparing towels for normal delivery surgical kits in Examples 1-3 Example 4 A towel for a normal delivery surgical kit. The difference between this embodiment and embodiment 1 is that the activated carbon is modified activated carbon, which is prepared by the following method: 1) 70 g of activated carbon (average particle size of 200 nm) was soaked in hydrogen peroxide (mass fraction of 20%), filtered, and dried to obtain hydroxylated activated carbon; 2) Mix hydroxylated activated carbon, 40 g of maleic anhydride, 20 g of polyether polyol, 1 g of initiator (propylene glycol) and 200 g of solvent (benzoyl peroxide), stir at 80° C. for 2 h, filter and dry to obtain grafted activated carbon; 3) The grafted activated carbon and 20 g of the first low-density polyethylene are melt-kneaded to obtain modified activated carbon.
[0040] The molecular weight of the first low-density polyethylene is 50,000.
[0041] The molecular weight of the polyether polyol is 2,000.
[0042] Example 5 A towel for a normal delivery surgical kit. The difference between this embodiment and embodiment 1 is that the activated carbon is modified activated carbon, which is prepared by the following method: 1) 150 g of activated carbon (average particle size of 200 nm) was soaked in hydrogen peroxide (mass fraction of 20%), filtered, and dried to obtain hydroxylated activated carbon; 2) Mix hydroxylated activated carbon, 60 g of maleic anhydride, 50 g of polyether polyol, 2 g of initiator (lauroyl peroxide) and 200 g of solvent (propylene glycol), stir at 95° C. for 3 h, filter and dry to obtain grafted activated carbon; 3) The grafted activated carbon and 30 g of the first low-density polyethylene were melt-kneaded to obtain modified activated carbon.
[0043] The molecular weight of the first low-density polyethylene is 50,000.
[0044] The molecular weight of the polyether polyol is 5,000.
[0045] Example 6 A towel for a normal delivery surgical kit. The difference between this embodiment and embodiment 1 is that the average particle size of the activated carbon is 100 nm.
[0046] Example 7 A towel for a normal delivery surgical kit. The difference between this embodiment and embodiment 1 is that the average particle size of the activated carbon is 1000 nm.
[0047] Example 8 A towel for a normal delivery surgical kit. The difference between this embodiment and embodiment 1 is that the particle size of the spherical microporous silica gel is 100-200 mesh, the pore volume of the internal structure is 0.8-1.3 ml / g, and the pore size is 80-120A.
[0048] Example 9 A towel for a normal delivery surgical kit. The difference between this embodiment and embodiment 1 is that the polyethylene is obtained by mixing a second low-density polyethylene and a high-density polyethylene in a weight ratio of 4:9.
[0049] The molecular weight of the second low-density polyethylene is 50,000, and the molecular weight of the high-density polyethylene is 200,000.
[0050] Example 10 A towel for a normal delivery surgical kit. The difference between this embodiment and embodiment 4 is that the polyethylene is obtained by mixing a second low-density polyethylene and a high-density polyethylene in a weight ratio of 6:9.
[0051] The molecular weight of the second low-density polyethylene is 50,000, and the molecular weight of the high-density polyethylene is 200,000.
[0052] Embodiment 11 A towel for a normal delivery surgical kit. The difference between this embodiment and embodiment 1 is that the molecular weight of the polyethylene is 200,000.
[0053] Example 12 A towel for a normal delivery surgical kit. The difference between this embodiment and embodiment 1 is that the styrene content in the ASB resin is 30%, the acrylonitrile content is 40%, and the butadiene content is 40%.
[0054] Comparative Example Comparative Example 1 A towel for a normal delivery surgical kit. The difference between this comparative example and Example 1 is that talcum powder is used instead of spherical microporous silica gel.
[0055] Comparative Example 2 A towel for a normal delivery surgical kit. The difference between this comparative example and Example 1 is that ceramic powder is used instead of activated carbon.
[0056] Comparative Example 3 A towel for a normal delivery surgical kit. The difference between this comparative example and Example 1 is that starch is used instead of chitosan.
[0057] The starch is corn starch.
[0058] Comparative Example 4 A towel for a normal delivery surgical kit. The difference between this comparative example and Example 1 is that epoxidized soybean oil is used instead of hydrogenated castor oil.
[0059] Comparative Example 5 A towel for a normal delivery surgical kit. The difference between this comparative example and Example 1 is that lecithin is used instead of glycerol monostearate.
[0060] Comparative Example 6 A towel for a normal delivery surgical kit. The difference between this comparative example and Example 1 is that lecithin is used instead of pentaerythritol stearate.
[0061] Comparative Example 7 A towel for a normal delivery surgical kit. The difference between this comparative example and Example 1 is that homopolypropylene is used instead of polyethylene.
[0062] The molecular weight of homopolypropylene is 5,000.
[0063] Comparative Example 8 A towel for a normal delivery surgical kit. The difference between this comparative example and Example 1 is that PET resin is used instead of ABS resin.
[0064] PET resin was purchased from Renhong Plastic Raw Materials Business Department in Zhangmutou, Dongguan City. The brand is Dow, USA, and the grade is FR543NC.
[0065] Detection method / test method Towels for normal delivery surgical kits were prepared using Examples 1-12 and Comparative Examples 1-8, and cut into samples with a length*width*thickness of 50 mm*50 mm*1 mm.
[0066] Absorption test: Use 20 ml of fresh pig blood and dilute it to 200 ml with water, add the test liquid, fold the sample in half, curl it into a cylinder, put it into the test liquid, and record the time it takes for the test liquid to be completely absorbed. If it is not absorbed within 120 seconds, it means that the absorption effect is poor, and the samples of this embodiment or comparative example are not subjected to other tests.
[0067] Antibacterial test: Test in accordance with GB / T20944.3-2008.
[0068] Softness test: According to the test method in GB / T 18318.1-2009 "Determination of flexural properties of textiles", the flexural strength of the fabric is tested. The smaller the flexural strength, the better the softness. Test and record the test results.
[0069] Tear strength test: Tested according to HG2-167-65 standard. The experimental data are shown in Table 2: Table 2 Experimental data of Examples 1-12 and Comparative Examples 1-8 It can be seen from Examples 1-12 and Comparative Examples 1-8 in combination with Table 2 that the towel used for the normal delivery surgical kit prepared by the formula in the present application has good absorption performance, antibacterial performance, softness and tear strength.
[0070] By comparing Example 1 with Comparative Examples 1-2, the absorption time of the test liquid in Comparative Example 1 exceeds 120 seconds, and the absorption time of the test liquid in Comparative Example 2 is much longer than that in Example 1; the antibacterial performance in Comparative Example 2 is lower than that in Example 1; and the softness in Comparative Example 2 is lower than that in Example 1. It can be seen from Example 1 and Comparative Examples 1-2 that in the present application, by preparing the towel with spherical microporous silica gel and activated carbon, the absorption performance, antibacterial performance and softness of the towel can be further improved.
[0071] By comparing Example 1 with Comparative Examples 3-4, the time for absorbing the test liquid in Comparative Examples 3-4 is longer than that in Example 1; the antibacterial performance in Comparative Examples 3-4 is lower than that in Example 1; and the softness in Comparative Examples 3-4 is lower than that in Example 1. It can be seen from Example 1 and Comparative Examples 3-4 that in the present application, by preparing the towel with the participation of spherical microporous silica gel and activated carbon, the absorption performance, antibacterial performance and softness of the towel can be further improved.
[0072] By comparing Example 1 with Comparative Examples 5-6, the time for Comparative Example 5-6 to absorb the test liquid is longer than that of Example 1; the antibacterial performance in Comparative Example 5-6 is lower than that in Example 1; the softness in Comparative Example 5-6 is lower than that in Example 1; and the breaking strength in Comparative Example 5-6 is lower than that in Example 1. It can be seen from Example 1 and Comparative Examples 5-6 that the absorption performance, antibacterial performance, softness and breaking strength of the towel can be further improved by using glycerol monostearate and pentaerythritol stearate together.
[0073] By comparing Example 1 with Comparative Examples 7-8, the time for Comparative Examples 7-8 to absorb the test liquid is longer than that of Example 1; the antibacterial performance of Comparative Examples 7-8 is lower than that of Example 1; the softness of Comparative Examples 7-8 is lower than that of Example 1; and the breaking strength of Comparative Examples 5-6 is lower than that of Example 1. It can be seen from Example 1 and Comparative Examples 7-8 that the absorption performance, antibacterial performance, softness and breaking strength of the towel can be further improved by using polyethylene and ABS resin together.
[0074] By comparing Example 1 with Example 4-5, the time for Example 4-5 to absorb the test liquid is shorter than that of Example 1; the antibacterial performance in Example 4-5 is higher than that in Example 1; the softness in Example 4-5 is higher than that in Example 1; and the breaking strength in Example 4-5 is higher than that in Example 1. It can be seen from Example 1 and Example 4-5 that modifying the activated carbon by the method of the present application is beneficial to improving the absorption performance, antibacterial performance, softness and breaking strength of the towel.
[0075] By comparing Example 1 with Examples 6-7, the time for Example 6-7 to absorb the test liquid is longer than that of Example 1; the antibacterial performance in Example 6 is lower than that in Example 1; the softness in Examples 6-7 is lower than that in Example 1; and the breaking strength in Example 6 is lower than that in Example 1. It can be seen from Examples 1 and 6-7 that the absorption performance, antibacterial performance, softness and breaking strength of the towel can be improved by optimizing the particle size of the activated carbon.
[0076] By comparing Example 1 with Example 8, the time taken for Example 8 to absorb the test liquid is longer than that of Example 1; the softness of Example 8 is lower than that of Example 1; and the breaking strength of Example 8 is lower than that of Example 1. It can be seen from Examples 1 and 8 that the absorption performance, softness and breaking strength of the towel can be improved by optimizing the particle size of the activated carbon.
[0077] By comparing Example 1 with Examples 9-10, the time taken by Examples 9-10 to absorb the test liquid is shorter than that of Example 1; the softness in Examples 9-10 is higher than that in Example 1; and the breaking strength in Examples 9-10 is higher than that in Example 1. It can be seen from Examples 1 and 9-10 that the absorption performance, softness and breaking strength of the towel can be improved by optimizing the type and amount of polyethylene.
[0078] By comparing Example 1 with Examples 11-12, the time taken by Examples 11-12 to absorb the test liquid is longer than that of Example 1; the softness in Examples 11-12 is lower than that in Example 1; and the breaking strength in Example 12 is lower than that in Example 1. It can be seen from Examples 1 and 11-12 that the absorption performance, softness and breaking strength of the towel can be improved by optimizing the parameters of polyethylene and ASB resin.
[0079] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A towel for a normal delivery surgical kit, characterized in that: Prepared from the following raw materials in weight percentage: Polyethylene 30-40% ABS resin 10-15% Spherical microporous silica gel 10-20% Glyceryl monostearate 4-6% Pentaerythritol stearate 3-5% Hydrogenated castor oil 3-6% Compatibilizer 1-2% Chitosan 6-9% The remainder is activated carbon.
2. A towel for a normal delivery surgical kit according to claim 1, characterized in that: The activated carbon is modified activated carbon, which is prepared by the following method: 1) Soaking the activated carbon in hydrogen peroxide, filtering, and drying to obtain hydroxylated activated carbon; 2) Mix the hydroxylated activated carbon, maleic anhydride, polyether polyol, initiator and solvent, stir at 80-95°C for 2-3h, filter and dry to obtain grafted activated carbon; 3) Melting and kneading the grafted activated carbon and the first low-density polyethylene to obtain modified activated carbon.
3. A towel for a normal delivery surgical kit according to claim 2, characterized in that: The weight ratio of the activated carbon, the maleic anhydride, the polyether polyol, the initiator, the solvent and the first low-density polyethylene is (7-15): (4-6): (2-5): (0.1-0.2): 20: (2-3).
4. A towel for a normal delivery surgical kit according to claim 3, characterized in that: The average molecular weight of the polyether polyol is 2000-5000.
5. The towel for a normal delivery surgical kit according to claim 1, characterized in that: The average particle size of the activated carbon is 200-800nm.
6. A towel for a normal delivery surgical kit according to claim 1, characterized in that: The particle size of the spherical microporous silica gel is 300-400 meshes, the pore volume of the internal structure is 0.8-1.3 ml / g, and the pore size is 80-120A.
7. A towel for a normal delivery surgical kit according to claim 1, characterized in that: The polyethylene is obtained by mixing a second low-density polyethylene and a high-density polyethylene in a weight ratio of (4-6):
9.
8. The towel for a normal delivery surgical kit according to claim 1, characterized in that: The ASB resin contains 40-50% styrene, 10-30% acrylonitrile and 30-40% butadiene.
9. A method for preparing a towel for a normal delivery operation pack as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: S1, mixing polyethylene, ABS resin, spherical microporous silica gel, glycerol monostearate, pentaerythritol stearate, hydrogenated castor oil, a compatibilizer, chitosan and activated carbon to obtain a mixture; S2, feeding the mixed material into a twin-screw extruder to melt into a mixed melt; S3, feeding the mixed melt into a spinning machine, spraying it out from a spinneret to form filaments, and then cooling, stretching, and winding it through air blowing to obtain fibers; S4, combing the composite fibers into a web, and then subjecting the web to hydroentanglement and drying to obtain a towel for a normal delivery surgical kit.
10. The method for preparing a towel for a normal delivery operation pack according to claim 9, characterized in that: In step S2, the temperatures of the heating zones of the twin-screw extruder are: 180-190°C for zones 1 to 3, 210-220°C for zones 4 to 6, 220-230°C for zones 7 to 8, and 210-220°C for zones 9 to 10.
Citation Information
Patent Citations
Cloth base material for surgical hole towels and method for preparing cloth base material
CN106965514A
Preparation method of modified biomass towel
CN108505337A
Disposable obstetrical operating towel
CN202386806U
Hole towel for delivery of pregnant woman
CN220917487U